PENGGUNAAN PERASAN JERUK NIPIS (Citrus aurantifolia) DALAM MENGHAMBAT BAKTERI Escherichia coli PADA BAHAN PANGAN - Zainal Berlian; Awalul Fatiqin; eka agustina (Bioilmi: Jurnal Pendidikan, 2016)
Bacteria in food can result from the sale of foods that do not pay attention to hygiene and safety. Pathogenic bacteria in food can cause illness gastroenteris/digestion. One of the ways to prevent the escape of pathogens is antibacterial compounds . Lemon (Citrus aurantifolia) contained many chemical compounds that can inhibit the growth of bacteria such as flavonoids and saponin. This study aims to isolate bacteria from food such as fish and chicken as a test of the effectiveness of lemon on the growth of bacteria. The study was conducted on April 2016 in MIPA (Science) Laboratory of UIN Raden Fatah Palembang and the Center for Health Laboratory Palembang. The research method is experimental laboratory used as a pour plate in order to make the diffusion were analyzed qualitatively. Using test bacteria Escherichia coli from food that is tested by agar diffusion method for determining the concentration of lemon juice on the growth of bacteria. The results showed that lemon juice can inhibit the growth of E. coli bacteria that is at a concentration of 25% average of 3,2 colonies of bacteria/gram; 50% mean bacterial concentration of 2,4 colonies/gram; 7% of the average bacterial concentration of 4,2% and 100% means bacterial concentration of 0,8 colonies/gram. Lemonsqueezemost effectively inhibits bacteria at concentrations of 100%.